Financing National Defense : policy and process - Jones, L. R. (Research in public management., 2012)
Assesses the numerous factors, including those that characterise the complex budget review and appropriation decision making dynamics of Congress, that make US defence finance and budgeting different from any other system in the world. In addition, the book compares US defence policy and budgeting to other nations in different regions of the globe.